Lupus Erytematous Syndrome and Anti Phospolipid Syndrome in a 44-Year-Old Man - Aqsha Tiara Viazelda; I Nyoman Suarjana (Journal of Social Research, 2025)
Antiphospholipid syndrome (APS) is a blood clotting condition characterized by thrombosis and obstetric disorders, more common in women. This case is rarely found in men due to vague symptoms. We reported a 34-year-old male patient who was admitted to Ulin Hospital on April 6, 2022 with complaints of headache, joint pain, and a history of autoimmune disorders. The patient develops cerebrovascular conditions at a young age. The diagnosis is made based on an anamnesis, physical examination, laboratory, and CT Scan, which shows Systemic Lupus Erytematous with APS. Laboratory results showed increased leukocytes, cholesterol, and coagulation, as well as high anticoagulant lupus. The therapies provided include methyl prednisolone, hyloquin, Myfortic, and the anticoagulant warfarin with a target of INR 2-3. The manifestations of APS and Lupus Erytematous vary, so a proper clinical approach is required. The diagnosis of APS in men is often overlooked due to the lack of obvious obstetric symptoms. Without supporting examinations, treatment cannot be carried out effectively, which can worsen the patient's condition. Patients are required to routinely monitor INR for anticoagulants, and evaluations are required for laboratory examinations to prevent economic losses.